As Missões Geográficas (1883-1940). Construção de um Documento Cartográfico - Santos, Paula Cristina (Africana Studia, 2020)
After the historical cycle of the discoveries, the Portuguese cartography was mainly dedicated to continental areas, achieving special importance in the beginning of the XVIII century with the production of Brazilian maps and with work concerning delimitation of frontiers. With the independence of the American colonies the attention of the politically and economically dominating European countries was transferred to Africa. At the Berlin International Conference, in 1884, it was announced, the principle of the “effective occupation” as a way to legitimate an African territory, recognising the geographic knowledge instead of historical rights. To obtain that knowledge the Geographic Missions were created by the Cartography Commission established by the Portuguese government in April 1883.